Validation of regional competitiveness indicators for the Southern Tagalog Region - Abansi, Corazon L. (Talas, 2003)
This study was conducted to validate established indicators for regional competitiveness, with specific application to the Southern Tagalog Region. Relevant economic theories guided the establishment of major competitiveness indicators, consisting of the following: factor conditions, demand conditions, economic dynamism and public goods and services.